(untitled) (Research, Society and Development, 2022)
The effect of defoliation levels (5, 10, 15, 20, 25 and 30 cm above soil level) on dry matter (DM) yield and morphogenetic and structural characteristics of Axonopus aureus was evaluated under field conditions in Roraima´s savannas. The effects of defoliation levels on the DM yields, absolute growth rate, number of leaves/plant, medium blade length, leaf area, leaf appearance and elongation rates were quadratics and maximum values recorded with cutting at 19.2; 17.5; 20.7; 27.2; 24.3; 20.5 e 25.9 cm above soil level. The population tiller density was directly proportional to the level of defoliation, while the opposite occurred for to leaf senescence rate. Apical meristem removing percentage was higher with increasing defoliation level. Aftermath regrowth showed close negative correlation with defoliation level. Pastures of A. aureus managed under residues between 15 and 25 cm above the ground provide greater productivity and efficiency of forage use, greater tissue renewal and a more favorable canopy structure for grazing.